Verteporfin Is a Promising Anti-Tumor Agent for Cervical Carcinoma by Targeting Endoplasmic Reticulum Stress Pathway - Wang, Meng; Liu, Chang; Li, Yuehan; Zhang, Qiulin; Zhu, Lixia; Fang, Zishui; Jin, Lei (Frontiers in Oncology, 2020)
Accumulated evidence has shown that the photosensitizer Verteporfin (VP) may be an ideal agent for various cancer types. However, the effect and mechanism of VP on human cervical carcinoma remain rudimentary. The aim of this study was to investigate the effect of VP on human cervical carcinoma cells (HeLa and SiHa cells) and to elucidate the possible mechanism. CCK-8, wound healing assay, flow cytometry analysis, western blotting, TUNEL staining were performed to evaluate the effects of VP on HeLa and SiHa cells in vitro as well as in vivo on a xenograft model. In addition, the role of endoplasmic reticulum (ER) stress in VP-induced apoptosis was investigated using RT-qPCR and western blotting. The results showed that the viability of HeLa and SiHa cells was suppressed by VP in dose- and time-dependent manners. Compared with the control group, apoptosis rates were higher with stronger TUNEL fluorescence signals in the experimental group, which substantiated that VP induced apoptosis at both 2D and 3D cell levels. Besides, VP can squelch the growth of tumors in both sizes and weights on the xenograft models without impairing ovarian reserve. Mechanism studies demonstrated that VP activated ER stress by upregulating the expression of GRP78, CHOP, and Caspase-12, and VP-induced apoptosis can be alleviated when ER stress pathway was inhibited. Our results provided a foundation for repurposing VP as a promising agent for cervical cancer patients without obvious reproductive toxicity by targeting ER stress pathway, and more researches are required to support its application in clinical practice.